2011
DOI: 10.1038/mp.2010.133
|View full text |Cite
|
Sign up to set email alerts
|

Resting leukocyte telomerase activity is elevated in major depression and predicts treatment response

Abstract: Telomeres are DNA-protein complexes that cap linear DNA strands, protecting DNA from damage. When telomeres critically shorten, cells become susceptible to senescence and apoptosis. Telomerase, a cellular ribonucleoprotein enzyme, rebuilds the length of telomeres and promotes cellular viability. Leukocyte telomeres are reportedly shortened in major depression, but telomerase activity in depression has not been previously reported. Further, there are no published reports of the effects of antidepressants on tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
111
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 74 publications
15
111
3
2
Order By: Relevance
“…Mechanisms related to oxidative stress, cellular metabolism and genome integrity, either through repair or maintenance of proper telomere length for instance, are current topics of research. 64,82-85 The brain and neuronal systems specificities of these biological processes represent unique areas of investigation for psychiatric and or neurological disorders. Another important topic of further investigation relates to the individual variability in age-related vulnerability to develop functional declines and associated disease symptoms, including LLD.…”
Section: Summary Conclusion and Future Directionsmentioning
confidence: 99%
“…Mechanisms related to oxidative stress, cellular metabolism and genome integrity, either through repair or maintenance of proper telomere length for instance, are current topics of research. 64,82-85 The brain and neuronal systems specificities of these biological processes represent unique areas of investigation for psychiatric and or neurological disorders. Another important topic of further investigation relates to the individual variability in age-related vulnerability to develop functional declines and associated disease symptoms, including LLD.…”
Section: Summary Conclusion and Future Directionsmentioning
confidence: 99%
“…Higher telomerase, while probably always beneficial for telomere protection, might also serve as an indicator of a high level of cellular stress. Telomerase appears to increase during acute stress (43) and certain states of chronic adversity, such as low education, depression, and caregiving (48)(49)(50), presumably to combat oxidative stress and to protect the telomere. In depressed people, although they had elevated telomerase at baseline, treatment with an antidepressant led to further increases in telomerase activity, and this telomerase increase was associated with a greater reduction in depressive symptoms (49).…”
Section: Caveats: Telomere Length and Telomerase Can Increase Or Decrmentioning
confidence: 99%
“…For instance, Stein and colleagues (2013) reported that individuals with SAD were at greater risk than healthy individuals to be affected by hypertension. Also, there is evidence linking accelerated cellular aging to stress (Blackburn, Epel, & Lin, 2015;Epel et al, 2004) as well as psychiatric disorders such as MDD (Verhoeven et al, 2014;Wolkowitz et al, 2012) and anxiety disorders (Verhoeven et al, 2015). In a large cohort, Verhoeven et al (2015) found that individuals with anxiety disorders (including SAD) had shorter leukocyte telomeres relative to healthy controls.…”
Section: Somatic Disordersmentioning
confidence: 99%